Pengaruh Tingkat Pendidikan, Pengetahuan, Sikap dan Terpaan Iklan Layanan Masyarakat KB Versi Shireen Sungkar dan Teuku Wisnu di TV terhadap Perilaku KB pada Wanita atau Pria dalam Usia Subur - Putri, Puri Kusuma Dwi (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2012)
AbstractThis study examinse level of education, knowledge, attitude and exposure to public service announcement of family planning which is involving fertile woman and man as sample. The coefficien of determination of this study is 34,7. It show that level of knowledge affect the behaviour of family planning behaviour. The result of this research show that level of education, level of knowledge and public service advertisingâ€™s exposure has impacted womanâ€™s behaviour over family planning.Â Keywords: family planning, knowledge affect the behaviour